Wireless Local Area Network : The New Communication Network Approach in the UUM Campus - Ooi, See Kun (2003)
This paper addresses the Wireless Local Area Network (WLAN) in Universiti Utara Malaysia. Universiti Utara Malaysia is the one of the public university located in Sintok, Kedah. This campus now already be implemented the concept wired university. The wireless system for Local Area Network (LAN) is an important landmark in the history of the Internet and electronic applications. It opens up existing systems, databases and intranets to mobile equipment such as telephones and hand-held terminals through a graphical customer interface. The most important benefit of WLAN is that it is independent of different mobile technologies that are used in different parts of the world. The recent increase in mobile computing technologies and projects in the enterprise environment has resulted in extensive use of numerous point-to-point products that cover only a small part of the total mobile and wireless infrastructure that is required. As the wireless local area network is getting more and more important to the infrastructure network, the objectives of this paper are to compare the wired LAN and wireless LAN in the UUM and to identify the strategic locations for implementing the wireless local area network in UUM.